Digital Literacy and the Development of Digital Education - Nazarova, Elena; Nazarov, Alexander (KnE Social Sciences, 2021)
Based on the concept of a digital turn in sociology proposed by Professor S. Kravchenko, the author, using the example of specific sociological studies of Russian research centers, analyzes the influence of the level of digital literacy of the population on the prospects of digital transformations in society. Digital literacy is considered as an integral indicator, including information, technical, communicative and innovative component. In addition to age and gender differentiation, the level of digital literacy is also affected by settlement and territorial factors, confirming that there is an urgent problem of digital inequality. With the ethical side of information literacy, the situation is also ambiguous. This indicator shows how deeply a person reflects on the information found and used. 45% do not think about the benefits and harms of the information they receive on the Internet. The quality of information also becomes a very revealing factor — the majority of respondents are critical to the information received and its sources. More than 70% admit that the media they have chosen may not always provide information reliably. Unexpectedly, in addition to the social group of people with higher education, the greatest skepticism in this regard is also characteristic of young people. Information literacy of the younger generation and lower computer literacy of the older generation reveal a deformation of the socialization process due to the emergence of the phenomenon of “spiritual distance” between these generations. Keywords: digitalization, a digital turn in sociology, digital literacy, information literacy